Correlation among sleep quality, physical frailty and cognitive function of the older adults in China: the mediating role - Peng, Shuzhi; Chen, Yanping; Li, Jie; Wang, Yan; Liu, Xingyue; Wang, Ying; Gu, Sainan; Pei, Mengyun; Zhang, Peng (Frontiers in Public Health, 2023)
Objective To explore the correlation among sleep quality, physical frailty, and cognitive function in the older adults in community, and to explore the mediating role of sleep quality. Methods A total of 1182 community-based older adults were investigated with frailty phenotype (FP), Pittsburgh sleep quality index (PISQI), Montreal cognitive assessment (MoCA) and self-made general information questionnaire. Results The incidence of physical frailty among the older adults in the community was 25.8% and the incidence of cognitive decline was 19.5%. Cognitive function was negatively correlated with physical frailty (r=−0.236, p<0.01) and sleep quality (r =−0.558, p<0.01). Sleep quality was positively correlated with physical frailty (r=0.337, p<0.01). Conclusion The physical frailty of the older adults has a direct prediction effect on cognitive function, and is regulated by the mediating role of sleep quality. Sleep quality partially mediates the relationship between cognitive dysfunction and physical frailty, which is a new insight into the study of cognition and physical frailty in the older adults. In the future, we can take measures to improve the sleep quality of the older adults, so as to reduce the occurrence of cognitive dysfunction and physical frailty of the older adults.